Photodetectors: Interlayer Coupling Induced Infrared Response in WS2/MoS2 Heterostructures Enhanced by Surface Plasmon Resonance (Adv. Funct. Mater. 22/2018). (28th May 2018) - Wang, Guichao; Li, Liang; Fan, Weihao; Wang, Renyan; Zhou, Shasha; Lü, Jing‐Tao; Gan, Lin; Zhai, Tianyou
Abstract : In article number1800339, infrared photodetectors based on WS2 /MoS2 heterostructures aere reported by Lin Gan, and Tianyou Zhai for the first time. WS2 and MoS2 show no infrared response (1030 nm) alone, but strong interlayer coupling shrinks the energy interval in the heterojunction area, rendering the heterostructures with longer wavelength detection ability compared to the individual components.